Multiple Hereditary Exostosis: A Case Study - Gutta Charith; Gopinath Menon; Ashok Thudukuchi Ramanathan; Sitsabesan Chokkalingam; Viveksheel Bhatti; Revanth T (Journal of Orthopedics and Joint Surgery)
Forearm deformities in children are challenging to treat. Presentation and manifestations of multiple hereditary exostosis presenting with forearm deformity with detailed approach and management are discussed in this case report.